Application of Learning Media Assisted with Improving Science Learning Outcomes through Quizz Media in Grade IV Students at SDN Melayu Muhammadiyah - Audrian Ahmad; Nurannisya Nurannisya; Julfiani Julfiani; Randy Saputra Mahmud; Wahyudi Wahyudi (Universitas Muhammadiyah Enrekang, 2024)
This research is motivated by the low learning outcomes of students in class IV C in the subject of science and natural sciences. Based on the results of the pre-cycle, the percentage value was 35%. Of the 20 students, only 7 students completed the learning with an average class value of 67.1. This is due to the lack of variation in teacher assessment methods and media in learning. The purpose of this study was to determine the increase in student learning outcomes using quizizz media in the subject of science and natural sciences for class IV at SDN Melayu Muhammadiyah. The research method used was PTK (Classroom Action Research) research using the Kurt Lewin model. This study was conducted in two cycles. Data collection techniques used by researchers were observation, interviews, documentation, and tests using quizizz media. Data analysis used quantitative analysis with descriptive. The results showed that student learning outcomes after implementing quizizz media increased. In cycle I, learning completion was obtained by 65% ​​(13 students), while the incomplete value obtained by students was 35% (7 students) with an average value of 74 (sufficient). In cycle II, the learning completion rate was 90% (18 students), while the incomplete value was 10% (2 students) with an average value of 91.75 (very good). From these data, it can be said that the quizizz paper mode media can improve student learning outcomes in the subject of science class IV C SDN Melayu Muhammadiyah